2016
DOI: 10.1002/mrm.26369
|View full text |Cite
|
Sign up to set email alerts
|

Suitable reference tissues for quantitative susceptibility mapping of the brain

Abstract: The internal capsule and CSF appear to be the most suitable reference regions for QSM of the brain in the melanoma patients studied. Both showed virtually no dependence on age or disease and small variations among patients. Magn Reson Med 78:204-214, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 42 publications
(60 reference statements)
3
91
0
Order By: Relevance
“…We abided by the following principles when drawing the ROIs to avoid containing adjacent brain regions from separate ROIs: (1) draw all successive slices with a clear, visible boundary of the nucleus in the axial plane; (2) remove the first and last layers of the nucleus; (3) draw a pixel point inward to ensure that the region drawn is within the scope of the nucleus; and (4) avoid obvious vascular structures. The QSM values (referenced to the susceptibility in the bilateral posterior limb of the internal capsule, http://www.brainlabel.org) were calculated. Mean QSM values within each ROI in each group are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…We abided by the following principles when drawing the ROIs to avoid containing adjacent brain regions from separate ROIs: (1) draw all successive slices with a clear, visible boundary of the nucleus in the axial plane; (2) remove the first and last layers of the nucleus; (3) draw a pixel point inward to ensure that the region drawn is within the scope of the nucleus; and (4) avoid obvious vascular structures. The QSM values (referenced to the susceptibility in the bilateral posterior limb of the internal capsule, http://www.brainlabel.org) were calculated. Mean QSM values within each ROI in each group are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…NAWM masks were generated by subtracting the lesion masks from the supratentorial cerebral hemispheric white matter masks. In order to compare tissue QS between individuals, the CSF QS within the lateral ventricular atrium was selected as an internal reference [26]. …”
Section: Methodsmentioning
confidence: 99%
“…In the (human) brain, variability has been shown in a number of regions commonly used as references in QSM studies. CSF has been shown to have the smallest variability (mean susceptibility 10 ± 14 ppb), whereas in the same study the mean susceptibility of the white matter ranged from 6 ± 20 ppb to 28 ± 23 ppb depending on the location in which it was measured . Furthermore, it has been shown that the susceptibility of CSF can change under the administration of gases .…”
Section: Discussionmentioning
confidence: 81%